Niveles de ventas de Mburgos - Market y Licores de la ciudad de Babahoyo durante el periodo 2023. - Segarra Pizarro, Alexis Giovanny (2024)
The sales levels in a microenterprise that is dedicated to the purchase and sale of goods, also to the home service and payments of basic services, banking transactions, whose mission is to solve the needs in its entirety, in Babahoyo, oriented exclusively in the area of sales. In this context, sales not only contributes to income generation, but also guides sales levels by providing key data, improving or increasing profitability, market adaptability, strategies and a deep understanding of how the microenterprise distinguishes itself in the market. It even adds insights into daily sales, which is fundamental to effective sales levels and positioned with business goals. In addition, it focuses on analyzing how the microenterprise has prepared, applied and examined its sales projects to achieve its microenterprise goals. Likewise, various elements such as position in the microenterprise market through sales are inspected. It examines sales in the market, strategies, social networks and the use of digital tools. This point of view in sales is directly related to microenterprise strategies as it is the success in sales of goods, in services and this needs a lot of effective in this contour. The analysis focuses on understanding how these sales strategies contribute directly to the microenterprise objectives, being fundamental for the strengthening of the presence in the microenterprise market.